Developing efficient weed management practices for higher productivity and profitability in aerobic rice (Oryza sativa) cultivation - GHOSH, A; SINGH, R K; SINGH, O N; SAMAL, P (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted on weed management in aerobic rice (Oryza sativa L.) cultivation during dry season in 2013, 2014 and 2015. Efficacy of different weed management tools was compared for their weed suppression ability in the cultivation of an improved rice variety, Sahbhagi Dhan at aerobic soil situations. The study showed highest (around 60%) weed control efficiency (WCE) and lowest (around 15%) weed index (WI) with intensive weed management (IWM), which was, however, found an uneconomical option on account of higher cost of weed management. The most economically viable weed management tool was the combined practice of the application of pre-emergence weedicide, Butachlor @ 2.5 l/ha after three days of sowing followed by manual weeding at 4th week stage of crop growth accounting around 35% WCE and 22.12% WI. Grain yield was recorded significantly higher (3.70 - 3.89 t/ha) with IWM followed by 3.61 - 3.62 t/ha with twice manual weeding. However, combined practice of pre-emergence weedicide application followed by manual weeding, although produced comparatively less grain yield of 3.47 - 3.50 t/ha, resulted in higher net return of Rupees 15250.0 and B:C ratio of 1.48 for the lowest cost of weed management (Rupees 6075.0). Thus, the study could suggest the application of pre-emergence weedicide supplemented with one manual weeding as the efficient weed management tool that could effectively control weed population in aerobic rice cultivation.